Bile production features in case of ischemic-reperfusion syndrome of limbs, abdominal trauma complicated with massive blood loss - I. V. Kuzminskyi; V. O. Krylyuk; M. A. Maksymenko (Kazimierz Wielki University, 2018)
The level of total bile acids in bile decreased in the groups of experimental animals in comparison with the control group. In the group of animals with simulated ischemic-reperfusion injury level of total bile acids in bile reached the minimal values in on the 3rd day, increasing was showed after on the 7th day, however level still remained lower than in control group. In EG-2 and EG-3 there was a unidirectional decreasing of the index by the seventh day, but in EG-3 these changes were more significant. Consequently, the level of cholesterol in the bile due to simulated injuries decreased in EG-1 and reached the minimal values in on the 3rd day and slightly increased to the seventh day of observation. In EG-2 the index gradually increased to the seventh day of observation. In EG-3 the maximum increasing was observed until the third day, after which it was at the same level. The analysis of the obtained indices testifies to the negative influence of ischemic-reperfusion syndrome on the level of cholesterol in the bile. Described changes influenced the cholato-cholesterol ratio, which was decreasing in all experimental groups. The most significant changes were in EG-3 in which abdominal trauma and hypovolemic shock were combined with ischemic-reperfusion limb syndrome. In the conditions of an experimental trauma with an ischemic-reperfusion injury of the lower limbs, there is a violation of the indices of the biliary function of the liver, which manifest themselves as a significant reduction of the level of total bile acids in the bile with increasing cholesterol concentration.